MIRA: Automated Generation of Measurable Non-Functional Requirements and Test Scenarios Using Multi-Agent Systems and RAG - Vasconcelos, Ana Klyssia Martins; Moreira, Edson Rodrigo Pinheiro; Sousa, Rubens Abraão da Silva; Monteiro, Gustavo Cesar Venancio; Bandeira, Alan Portela; Souza, Jerffeson Teixeira de; Maia, Paulo Henrique Mendes; Santos, Ismayle de Sousa (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
The specification of Non-Functional Requirements (NFRs) is critical to software quality, but suffers from human subjectivity and the hallucination tendency of generic LLMs. This work addresses the gap in the automated generation of accurate and testable NFRs from high-level user stories. We propose MIRA, a multi-agent architecture based on Retrieval-Augmented Generation (RAG) that orchestrates the contextualized production of requirements and test scenarios. From 11 representative user stories, MIRA automatically generated 25 NFRs and 49 test scenarios across 10 functional domains. Validation with 15 software professionals, totaling 165 evaluations per dimension, demonstrated high clarity (µ = 4.45), measurability (µ = 4.39) and test adherence (µ = 4.47) on a 5-point Likert scale, with strong internal consistency (Cronbach’s α > 0.84). It is concluded that the approach mitigates generative inconsistencies, acting as an effective accelerator in the integration between requirements engineering and validation.